Legal Protection Against Victims Of The Crime Of Rapes Based On Justice Value - Tatik Zakiyati (UNISSULA Semarang, 2021)
There are so many women who experience sexual violence, especially rape, women can't do much to avoid it and are forced to let it happen. The judicial process is often only oriented towards giving punishment but does not pay attention to how to restore the condition of the victim. The problem will be even more complicated, where most of our society views that issues related to decency are still very taboo to be discussed in public, especially the issue of the crime of rape. This study uses a normative juridical approach. The results of this study are 1) the factors have not been implemented because the law, law enforcement officers, the culture of the community and the factors of the facilities or facilities that cause the rights of rape victims which should be regulated and integrated for the right to restitution and or compensation, legal assistance, psychologists, psychiatrists, religious experts or other experts who are able to restore the victim's confidence. 2) Whereas the obstacle that arises comes from the victim, namely the victim herself who wants not to be protected by the Police, because the rape victim refuses to report it. 3) Protection of witnesses and victims according to Law no. 13 of 2006 concerning the protection of witnesses and victims is to provide a sense of security to witnesses and/or victims in providing information in every criminal justice process. Religious experts or other experts who are able to restore the victim's trust. 2) Whereas the obstacle that arises comes from the victim, namely the victim herself who wants not to be protected by the Police, because the rape victim refuses to report it. 3) Protection of witnesses and victims according to Law no. 13 of 2006 concerning the protection of witnesses and victims is to provide a sense of security to witnesses and/or victims in providing information in every criminal justice process. Religious experts or other experts who are able to restore the victim's trust. 2) Whereas the obstacle that arises comes from the victim, namely the victim herself who wants not to be protected by the Police, because the rape victim refuses to report it. 3) Protection of witnesses and victims according to Law no. 13 of 2006 concerning the protection of witnesses and victims is to provide a sense of security to witnesses and/or victims in providing information in every criminal justice process.